Evaluating signalling and packet delivery cost for NDN producer’s mobility in smart & sustainable environment - Ahmed, Muhammed Zaharadeen; Hassan Abdalla Hashim, Aisha; Mohd. Ramli, Huda Adibah; Khalifa, Othman Omran; Hassan, Afaf Mirghani; Baba, Usman Ahmed (Institute of Advanced Scientific Research, 2020)
The number of Internet users increases every day across the globe. This motivates network service providers adopt various environmental best practices of implementing smart and sustainable initiatives. However, number of connecting devices exceed the requirements to achieve sustainable developmental goals as recommended by the United Nations. Research outputs projected that IP architecture only could not connect all computers, phones, cars, building etc. Therefore, NDN is introduced as one alternative to overcome these future challenges and be easily adopted with IoTs. In NDN, it is obvious that content producer has huge challenge of mobility and limited research is conducted in this regard. In this paper, mathematical analysis and simulation approach were used to verify performance of NDN producer mobility for signalling cost and packet delivery. Mathematical evaluation involves the use of definite integrals for easy determination of maximum and minimum cost of signalling and packet delivery. Movement of signal (handoff) and content success rates were evaluated under dissimilar network heterogeneity. These heterogenous changes are in form of vehicle speeds, producer’s formation (nodes), barriers in buildings, cameras, televisions etc that acts as content producers and consumers. Results presents better success rates in delivering heterogenous NDN content as compared to our benchmark and other literatures. Simulations also presents less content re-transmissions in situations where NDN contents pair with IP contents to shear resources.